An Effective Leadership Model for Madrasah Principals in Indonesia. - Musthan, Zulkifli (Pertanika Journal of Social Sciences & Humanities, 2019)
This study aims at creating an effective leadership model for madrasah (Private Islamic High Schools) principals in Indonesia and in doing so getting an overview of the characteristics that nurture visionary leadership which encompass noble character, intelligence, communication skills, entrepreneurial spirit, leaders that uphold deliberation and establish a madrasah culture that is conducive; all of which help in the implementation of dynamic leadership at Madrasah in Indonesia. The effective leadership model of the madrasah principal is independently developed by research through the methodology which is adapted from Borg's research and development procedures. The findings of this study; (1) identified character traits synonymous with noble character, intelligence, effective communication, strategies in maintaining open climates, strategies in having an entrepreneurial spirit, and strategies in shaping madrasah culture; (2) provided an overview of the effectiveness of the effective implementation of the madrasah principal leadership at Madrasah Aliyah that is related to traits that are common to (a) visionary leadership in an effective manner; (b) effective attitudes; (c) effective intelligence; (d) effective ability to communicate; (e) ability to maintain open climates; (f) ability to encourage entrepreneurial spirits; and (g) ability to shape madrasah culture. This madrasah leadership model can be used in madrasah in South Sulawesi, Indonesia.